2015
DOI: 10.1016/j.nrl.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Epigenética y epilepsia

Abstract: Identifying the epigenetic mechanisms involved in epilepsy is a promising line of research that will deliver more in-depth knowledge of epilepsy pathophysiology and treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Such changes could affect susceptibility to and development/maintenance of epilepsy. In fact, the detection of epigenetic modifications observed in both animal models and tissues from patients with temporal lobe epilepsy are encouraging a new line of research that may contribute substantially to our knowledge of epilepsy susceptibility[115]. The significant challenge is how to apply these approaches to investigate risk factors in IGE epilepsy, such as JME.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes could affect susceptibility to and development/maintenance of epilepsy. In fact, the detection of epigenetic modifications observed in both animal models and tissues from patients with temporal lobe epilepsy are encouraging a new line of research that may contribute substantially to our knowledge of epilepsy susceptibility[115]. The significant challenge is how to apply these approaches to investigate risk factors in IGE epilepsy, such as JME.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a hypothesis has been previously demonstrated that the aberrant alterations in gene expression results in aberrant hyperexcitability, which may cause repeated seizures . It is significant to note the epigenetic mechanisms previously delineated to characterize the development of drug resistance in epilepsy, during which the altered gene expression has a role to play during antiepileptic drug uptake . Here, our study highlighted the involvement of miR‐139‐5p in the translational suppression of MRP1, resulting in the inhibition of drug resistance in refractory epilepsy.…”
Section: Discussionmentioning
confidence: 57%
“…In addition, the neurodevelopment process also highly depends on DNA methylation (Gapp et al, 2014). Specifically, DNA methylation is observed at CpG islands in the mammalian genome, where it can modulate gene expression (Jones, 2012), through the addition of a methyl group to m 5 C molecules (Pulido Fontes et al, 2015). Brain DNA has one of the highest levels of m 5 Cs in human organs (Kriaucionis and Heintz, 2009; LaSalle et al, 2013), and DNA methylation is required for neuronal differentiation in mammals (Takizawa et al, 2001; Mohn et al, 2008).…”
Section: Canonical Epigenetics and Neurodevelopmentmentioning
confidence: 99%